Pengaruh Media Sosial Tik - Tok Terhadap Karater Siswa Sekolah Dasar - Zahidah Bashiroturrohmah; Sisika Martha Nur Cahyani; Andhita Risko Faristiana (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The Influence of Tik-Tok Social Media on the Character of Elementary School Students. In the era of globalization, there are technological developments. One of the problems that cannot be avoided and has become an important requirement in today's culture is the development of increasingly sophisticated technology. This study aims to determine the effect of social media relations on the character of fifth grade elementary school students in Jenang sub-district, Ponorogo district. The use of social media that will be researched is social media tik tok. This study uses a quantitative method, the data collection technique is by distributing online questionnaires to those who want to be studied. The sample studied was elementary school students in one of the Jenang sub-districts, Ponorogo district. The questionnaire was taken from 25 grade V elementary school students consisting of 12 boys and 13 girls. The research also involved one of the parents of fifth grade students and also the homeroom teacher of grade V, by conducting interviews with the people closest to them. We also conduct research for further research that requires information by making observations to directly observe the character and patterns of their social interaction after spending a lot of time playing social media. The results of this study indicate that there is an impact of the use of social media that can affect student character on development and learning patterns in grade 5 elementary school students, Jangan sub-district, Ponorogo district. This impact can lead to positive and negative impacts, where the positive impacts are more than the negative impacts. one of them is someone can hone creativity in creative editing, videos with music and writings that contain meaning in sentences. As well as being able to motivate others with videos and sentences that have meaning in one's life.